2018
DOI: 10.1002/jsc.2232
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the potential of the growth of e‐retailer based on impact of perceived value on trust for online purchases

Abstract: Customer satisfaction for online purchase and its subsequent influence on customer trust is a pivotal in the proliferation of online businesses that in turn can foster global and national economic growth. The significance of understanding perceived value in the context of online shopping is as important as is in the context of traditional shopping. Quantitative data were collected from customers, who have online shopping experience. The analysis, carried out using structural equation modeling, suggests that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Along with these changes, online stores are replacing traditional stores and a large part of customers' shopping is performed online (3); it is estimated that in 2017 alone, one billion six hundred and sixty million people worldwide have had at least one online purchase experience (4). Similarly, the results of a survey conducted in twenty-five different countries showed that, on average, 54% of daily, weekly and monthly customer purchases are done online (5). On the other hand, it is predicted that the turnover of ecommerce worldwide will reach more than four trillion dollars by 2020, indicating the importance and development of e-business in today's world (6).…”
Section: Introductionmentioning
confidence: 99%
“…Along with these changes, online stores are replacing traditional stores and a large part of customers' shopping is performed online (3); it is estimated that in 2017 alone, one billion six hundred and sixty million people worldwide have had at least one online purchase experience (4). Similarly, the results of a survey conducted in twenty-five different countries showed that, on average, 54% of daily, weekly and monthly customer purchases are done online (5). On the other hand, it is predicted that the turnover of ecommerce worldwide will reach more than four trillion dollars by 2020, indicating the importance and development of e-business in today's world (6).…”
Section: Introductionmentioning
confidence: 99%